PARTISIPASI POLITIK PEREMPUAN DI PARTAI DEMOKRAT PADA PEMILIHAN ANGGOTA LEGISLATIF 2014 KABUPATEN PARIGI MOUTONG - Idris, Amelia (Katalogis, 2016)
This study aims to identify and analyze the management of public transport levy. This research uses qualitative descriptive, in the opinion of Huntington and Nelson (2004: 16-19), consists of political participation in electoral activities, the activities of the lobby, in the activities of the organization, in a search for connection activity, and the activity of violence. Based on the analysis concludes that low women's political participation in electoral activities, the activities of the lobby, in the activities of the organization, in a search for connection activity, and the activity of violence. Generally candidates (candidates) female Democrats in the 2014 election, is the candidate imposed simply to qualify for a quota of 30% in order to follow the elections. Democratic party leaders felt difficulty finding female candidates, including as a member of the board. All requirements as female candidates prepared by party officials to campaign activities. It made the women candidates of the Democratic party Parigi Moutong district did not follow her activities to facilitate obtaining a majority vote, unless one candidate with the most votes but did not win a seat, because he is a social activist than as early childhood teachers.